FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PELAPORAN KEUANGAN TAHUNAN PERUSAHAAN (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar pada Bursa Efek Indonesia Tahun 2012-2013) - Upik Maharani; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
The aims of this research to test the company's annual financial reporting timeliness influenced by the effectiveness of the audit committee, the age of the company, Debt to Equity Ratio (DER), profitability and solvency. Annual financial reporting timeliness is measured using a dummy variable, the effectiveness of the audit committee effectiveness is measured using an index developed by Ika and Ghazali (2009), the age of the company is measured by how long the company is listed in the Indonesia Stock Exchange, DER proxied by Total Debt divided by Total Equity owned company, profitability is proxied by the ROA, while solvency is proxied by TDTA (Total Debt to Total Assets).The sample was 624 non-financial companies listed on the Stock Exchange during 2012-2013, which obtained by purposive sampling method. To examine the relationship variables of this research, used logistic regression analysis.The results showed that the effectiveness of the audit committee and profitability have a significant positive effect on the company's annual financial reporting timeliness. As for the age of the company, DER, and solvency show that these variables did not significantly influence the company's annual financial reporting timeliness.